2021
DOI: 10.1111/jre.12890
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use disorders are associated with higher prevalence of periodontitis in a rural area of Brazil

Abstract: Objective The aim of the present cross‐sectional study was to determine whether alcohol use disorders (AUD) are independently associated with severe and extent cases of periodontitis in individuals living in a rural area of Brazil. Methods A representative probability sample (N = 585) was evaluated using six‐site full‐mouth periodontal examination. AUD was assessed using the alcohol use disorders identification test (AUDIT) and considered in its unidimensional and bidimensional factor structures. The first add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…From a practical perspective, this indicates that public oral health initiatives should include alcohol as a target to reduce the socioeconomic burden associated with oral diseases, ultimately benefiting the most marginalised. Alcohol consumption was linked with periodontitis incidence and progression in middle-income countries 27,28 and among older adults, 28,29 highlighting a possible explanation to the poor OHRQoL found among BD respondents. Likewise, crossing the binge threshold increases the risk of acute harm and alcohol-related consequencessuch as blackouts, loss of control and role failure-which were also reported to be associated with severe periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From a practical perspective, this indicates that public oral health initiatives should include alcohol as a target to reduce the socioeconomic burden associated with oral diseases, ultimately benefiting the most marginalised. Alcohol consumption was linked with periodontitis incidence and progression in middle-income countries 27,28 and among older adults, 28,29 highlighting a possible explanation to the poor OHRQoL found among BD respondents. Likewise, crossing the binge threshold increases the risk of acute harm and alcohol-related consequencessuch as blackouts, loss of control and role failure-which were also reported to be associated with severe periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol consumption was linked with periodontitis incidence and progression in middle‐income countries 27,28 and among older adults, 28,29 highlighting a possible explanation to the poor OHRQoL found among BD respondents. Likewise, crossing the binge threshold increases the risk of acute harm and alcohol‐related consequences—such as blackouts, loss of control and role failure—which were also reported to be associated with severe periodontitis 29,30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also expect some recall and information biases inherent to self‐report measurements of alcohol consumption, and we assumed that respondents had kept the same drinking habits over time – however, people change their drinking behaviour during the life course and similar consumption levels do not necessarily lead to similar consequences, given the diversity in biopsychosocial status. In this respect, the amount of alcohol intake may not capture all domains of the association between alcohol misuse and tooth loss – that is, some alcohol use disorders characteristics, such as withdrawal and physical, mental and social consequences, might be independent of the volume of alcohol consumption (Visontay et al, 2020) but associated with tooth loss (Enberg et al, 2001; Oliveira et al, 2021). Lastly, we do not have access to data at municipality level, which would be important to assess the contextual determinants of alcohol consumption, such as alcohol outlet density, drinking contexts and alcohol policy, that possibly influence the individual consumption and ultimately playing a role in the oral health impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Among lifestyle factors related to periodontitis, alcohol intake has shown to be associated with its occurrence in cross-sectional studies, 6 , 7 , 8 and some pathways were suggested to explain this association: besides the fact that ethanol is a substrate for bacterial metabolism, 9 , 10 alcohol use overtime may create a favourable environment with sufficient energy for the growth of anaerobic periodontal pathogens due to disturbed host-bacterium interactions 11 and depletion of microbiota associated with periodontal health. 12 Although five systematic reviews had explored the impact of alcohol consumption on periodontal status, 13 , 14 , 15 , 16 , 17 it is not clear whether the described exposure impacts the presence or levels/proportions/overall quantity of specific pathogens, as well as the homeostatic integrity of the polymicrobial biofilm, which are likely to be altered prior to the development of clinically detectable disease.…”
Section: Introductionmentioning
confidence: 99%